The Seamless Integration of Digital Health Tools in Clinical Practice: A Professional's Guide - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare landscape is undergoing a profound transformation, driven by the rapid evolution of Digital Health Tools DHTs. These technologies, which encom...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics